Ovarian and paraovarian adrenal rest tumors are not uncommon in gonadectomy materials of historical congenital adrenal hyperplasia cases in childhood. Issue 1 (1st June 2022) - Yildiz, Melek; Bayram, Aysel; Bas, Firdevs; Karaman, Volkan; Toksoy, Guven; Poyrazoglu, Sukran; Soysal, Feryal Gun; Onder, Semen; Uyguner, Zehra Oya; Darendeliler, Feyza
Abstract: Objective: The aim of this study was to assess the prevalence of ovarian and paraovarian adrenal rest tumors (ARTs) in gonadectomy materials of a subgroup of congenital adrenal hyperplasia (CAH) patients. Methods: A total of 20 historical cases with clinical/molecular diagnosis of classical CAH were included in the study. All patients had 46, XX karyotype and underwent gonadectomy because of being raised as male. Results: Median age at diagnosis of CAH was 5.7 years and was markedly delayed. All patients revealed severe virilization. Bone age was significantly advanced, and bone age/chronological age ratio was increased with a median ratio of 1.8. Median age at the time of gonadectomy was 9.2 years. Ovarian and paraovarian ARTs were detected during the pathological evaluation of gonadectomy materials in four patients (20%) (two with simple virilizing 21-hydroxylase and two with 11-beta-hydroxylase deficiency) with previously normal pelvic imaging. In three cases with ARTs, paraovarian area was composed of medium-sized polygonal cells, with round or oval monomorphic nuclei and abundant granular eosinophilic cytoplasm which is characteristic of adrenocortical tissue. The fourth case had bilateral ovarian 'steroid cell tumors, not otherwise specified', and the tumor was accepted as benign. Except for the ARTs, heterotopic prostate and bilateral paratubal epididymis tissue were detected in a patient. Conclusions: Ovarian and paraovarian ARTs might be more common than previously described, especially among patients with excessive and prolonged adrenocorticotropic hormone exposure. These tumors could be detected histopathologically even if not detected by classical imaging methods.